2007
DOI: 10.1073/pnas.0702447104
|View full text |Cite
|
Sign up to set email alerts
|

Essential roles of the bHLH transcription factor Hrt2 in repression of atrial gene expression and maintenance of postnatal cardiac function

Abstract: congenital heart disease ͉ heart development ͉ heart failure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
139
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(145 citation statements)
references
References 53 publications
4
139
0
1
Order By: Relevance
“…1). However, deletion of hrt2/hey2 in murine cardiomyocytes causes ectopic atrial gene expression in the ventricle (30). This might be due to the difference of expression patterns of hrt2/hey2 and grl in mice versus fish.…”
Section: Discussionmentioning
confidence: 97%
“…1). However, deletion of hrt2/hey2 in murine cardiomyocytes causes ectopic atrial gene expression in the ventricle (30). This might be due to the difference of expression patterns of hrt2/hey2 and grl in mice versus fish.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, it is expected that implementing standardized protocols for antibody labeling and analysis should better permit reliable comparison of the efficiency of cardiomyogenesis and subtype identity among protocols. As the field continues to establish robust protocols for efficient cardiomyogenesis, future efforts to more fully define the cells generated from such protocols will include the analysis of maturation stage and chamber-restricted markers such as hairy-related transcription factors 1 and 2 (HRT1, HRT2 38,39 ), gap junction alpha-5 protein (GJA5, CX40 40 ), sarcolipin (SLN 41 ) natriuretic peptides A (NPPA 42,43 ), potassium voltage-gated channel subfamily E member 1 (KCNE1 44 ), T-box transcription factor TBX3 (TBX3 45 ),heart-and neural crest derivatives-expressed protein(HAND1, HAND2 [46][47][48] ), and potassium/sodium hyperpolarization-activated cyclic nucleotide-gated channel 4 (HCN4 [49][50][51] ), among others. For marker analysis, it is recommended that both mRNA and protein levels be measured when possible, as protein modifications, stability and turnover can affect the relationship between gene expression and protein abundance (e.g., TNNT2 in Figures 1B, 2E) and, during development, patterns of expression differ between mRNA and protein for some markers (reviewed in Franco et al 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HEY2-deficient embryos displayed a change in the expression patterns of GJA5, NPPA, and TBX5. 43,45,46 These genes have all previously been associated with AF. [47][48][49][50] Thus, several studies support our finding that BrS-associated genetic variants protect against AF.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43][44] Bezzina et al 27 found homozygous HEY2 knock-out embryos to have increased Na V 1.5 expression and a flattened transmural expression gradient of the channel in the cardiac ventricles. In HEY2 þ / À knock-out mice, the conduction velocity was increased in the right ventricle outflow tract (RVOT), and the action potential upstroke velocity was increased, indicating an increase in sodium channel peak current.…”
Section: Discussionmentioning
confidence: 99%